Biomass partitioning and yield components of individual tillers of rice (Oryza sativa) at different nitrogen levels - KRISHNAN, P; NAYAK, S K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during winter season (rabi) 1995-96 with rice (Oryza sativa L.) to investigate the distribution pattern of biomass among different tillers. The productive potential of individual tillers of 2 cultivars (’IR36’ medium tall and ’Swarnaprabha’ tall) at 4 different nitrogen levels (N0, N30, N60 and N90) were studied in terms of biomass partitioning, harvest index and proportion of high density grains. Vegetative phase partitioning of biomass in the mother shoot of’Swarnaprabha’ was more in the order of culm > leaf sheath > and leafblade. But in ’IR 36’ higher proportion was in leaf sheath followed by culm and leaf blade. High levels of nitrogen application resulted in more partitioning to leaf sheath than to culm. In general, mother shoot and primary tillers had high number offilled grains, harvest index and yield in both varieties. Increasing levels of nitrogen application resulted in more secondary tillers which contributed little to grain yield resulting in harvest index.